(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Now- a- days, it is essential having a good command over Englishlanguage and its proficiency. If we look over the students of higher secondaryclass regarding the said skill, then we find many questions and problems aboutthe efficiency & proficiency of English language and the basic skills ofthis language. According to my point of view the major problem of the saidstudents is that English language is only a school subject language and nottheir mother language or routine language and also not an operational too.Here, the investigator tries to find out the other ways of this problem viathis study.